The effectiveness and evaluation of conservation planning - Bottrill, Madeleine C.; Pressey, Robert L. (Conservation letters, 2012)
Investment of time and resources in conservation planning has grown exponentially in recent years; yet there has been limited evaluation of the benefits and costs of investing in planning exercises. Without evaluation, investments in planning are not accountable, decisions are not defensible, and learning from past experiences is limited. Bringing together information from published literature, planning documents, and new qualitative data from interviews with planners, we describe an evaluation framework for conservation planning to more fully address the potential range of outcomes, categorized across five types of capital: natural, financial, social, human, and institutional. We review the extent to which evidence supports these types of outcomes, and finish by considering the conceptual, operational, organizational, and policy implications of improved evaluation in planning. If conservation planning seeks to be effective, adaptive, and informative, then systems of evaluation must be considered from the outset of planning processes to support learning and improvement of outcomes.